The Effect of Acupressure on Pain Levels Kala I in Maternity Mothers - Sulistyowati, Nining; Trisnawati, Yeti (Jurnal EduHealth, 2022)
Most of the mothers who gave birth stated that they could not stand the pain that was felt, especially in the abdomen, waist, back and spread to the spine, so that the mother continued to feel pain during the first stage of labor. Contractions during labor can cause pain. Labor pain can cause stress that causes excessive release of hormones such as catecholamines and steroids. One method of reducing pain without drugs that can be given continuously, is cost-effective, and has a low risk, namely acupressure. Objective: To determine the effectiveness of acupressure therapy on reducing labor pain in the active phase of the first stage. This research is a Quasi Experimental Design with a One Group Pre-Post Test Design approach. The population in this study were all birth mothers who checked their pregnancies. The sampling technique was carried out by accidental sampling and a sample of 20 respondents was obtained. Collecting data by observing the acupressure treatment with the Numerical Rating Scale (NRS). Univariate analysis using frequency distribution and bivariate analysis using paired t test. The results of the study mean labor pain before being given acupressure was 6.48 and after being given acupressure was 3.84. There was an effect of acupressure techniques on active phase I labor pain (p–value 0.0001 <0.05) with a decrease of 2.64. Acupressure therapy can be applied to midwifery care for mothers in the first stage of labor which aims to reduce labor pain